Disproportionation of Nitric Oxide at a Surface‐Bound Nickel Porphyrinoid. (21st March 2022) - Stredansky, Matus; Moro, Stefania; Corva, Manuel; Sturmeit, Henning; Mischke, Valentin; Janas, David; Cojocariu, Iulia; Jugovac, Matteo; Cossaro, Albano; Verdini, Alberto; Floreano, Luca; Feng, Zhijing; et al.
Abstract: Uncommon metal oxidation states in porphyrinoid cofactors are responsible for the activity of many enzymes. The F430 and P450nor co‐factors, with their reduced Ni I ‐ and Fe III ‐containing tetrapyrrolic cores, are prototypical examples of biological systems involved in methane formation and in the reduction of nitric oxide, respectively. Herein, using a comprehensive range of experimental and theoretical methods, we raise evidence that nickel tetraphenyl porphyrins deposited in vacuo on a copper surface are reactive towards nitric oxide disproportionation at room temperature. The interpretation of the measurements is far from being straightforward due to the high reactivity of the different nitrogen oxides species (eventually present in the residual gas background) and of the possible reaction intermediates. The picture is detailed in order to disentangle the challenging complexity of the system, where even a small fraction of contamination can change the scenario. Abstract : Nickel tetraphenyl porphyrins deposited in vacuo on a copper surface are reactive towards nitric oxide disproportionation already at room temperature. The high chemical reactivity of nitrogen oxides species, eventually present in the residual gas background, and of the possible reaction intermediates yields a challenging complexity, where even a small fraction of contamination can change the scenario.